2016
DOI: 10.17159/sajs.2016/20150280
|View full text |Cite
|
Sign up to set email alerts
|

Stirred cell ultrafiltration of lignin from black liquor generated from South African kraft mills

Abstract: Ultrafiltration of lignin from black liquor was carried out in a stirred batch cell using polyethersulfone membranes. Parameters such as operating pressure, feed concentration, stirring rate and membrane cut-off size were varied and their effects on lignin retention and permeate flux were investigated. The operating pressure, feed concentration and stirring rate were varied in the ranges 150–350 kPa, 3–9% and 200–400 rpm, respectively. The membranes used had cut-off sizes of 5 kDa, 10 kDa and 20 kDa. A one-fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The greater retention reflected the compression of the probably formed gel layer at higher pressures, thus causing more of the spent sulfite liquor to reach the membrane surface. This vicious layer is responsible for the pre-sieving of the lignosulfonate molecules [6,16,42,52]. We found that the Reynolds number made no significant difference to the quantity of retained lignosulfonate.…”
Section: Resultsmentioning
confidence: 92%
“…The greater retention reflected the compression of the probably formed gel layer at higher pressures, thus causing more of the spent sulfite liquor to reach the membrane surface. This vicious layer is responsible for the pre-sieving of the lignosulfonate molecules [6,16,42,52]. We found that the Reynolds number made no significant difference to the quantity of retained lignosulfonate.…”
Section: Resultsmentioning
confidence: 92%